Clinical Efficacy and Technical Aspects of Endovideosurgical Treatment of Hiatal Hernia (Texas Journal of Medical Science, 2022)
Complications of mixed hernia often require surgical treatment. In asymptomatic patients, this treatment is controversial due to its difficult recovery and high recurrence rate reported in the long term. Classical surgical methods have an increased mortality associated with large incisions, long hospital stays, and slow recovery. Material and Methods: in the period from October 2001 to November 2007, we examined 39 patients with mixed hiatal hernia of the middle age of 65 years (35-78 years). In the LloydDavis position, the contents of the hernia are reduced, and the excess sac is resected. Diaphragmatic racks are sutured with non-absorbable material. The reinforcing mesh interfered with the repair of 7/39. It ends with partial or complete antireflux depending on the report. Results: the average operation time was 126 minutes; hospital stay 2.46 days. Perioperative complications are mainly cardiorespiratory. The patient died from accidental intestinal perforation during the intervention and late diagnosis. Gastroduodenal movement was performed by 12 months in 28 patients (71.7%). We find recurrence in 8 patients (20.5%). Four asymptomatic patients accidentally discovered in X-ray control. Three patients with pyrosis requiring treatment and one of the relapses required re-intervention for strangulation of gastric volvulus. Conclusions: laparoscopic surgery provides safety and efficiency, rapid postoperative recovery, minimal morbidity and comfortable stay. After surgery, a long recurrence gives the same results as with open surgery, although the installation of a mesh may mitigate its reduction.